The impact of the COVID-19 pandemic on the developmentof anxiety disorders - a literature review - Koch, Mateusz; Chmielowiec, Krzysztof; Grzywacz, Elżbieta; Suchanecka, Aleksandra; Masiak, Jolanta; Chmielowiec, Jolanta (Current Problems of Psychiatry, 2025)
Introduction: The COVID-19 is a disease caused by the SARS-CoV-2 virus. A number of psychological symptoms have been identified in people living during the COVID-19 pandemic. Most of them are associated with widely understood anxiety disorders, which have always been a significant problem for mental health. Materials and methods: The available literature was reviewed on the Pubmed platform and from other sources. The analysis included original studies, reviews, meta-analyzes and internet sources. The aim of the study was to review the literature on the relationship between the COVID-19 pandemic and the occurrence and severity of symptoms of anxiety disorders. Results: The studies conducted so far show that the COVID-19 pandemic has had a significant impact on the mental state of people around the world, especially in the area of anxiety disorders. Many studies indicate an increase in the prevalence of symptoms of generalized anxiety disorder. Research also indicates a greater incidence of post-traumatic stress disorder and panic disorder in society. Symptoms of somatization were also quite often observed in patients. However, the state of published studies indicates that the pandemic did not significantly affect the severity of symptoms associated with social phobia. In the context of phobic disorders, a new type has been formulated: COVID-19-related phobia. Conclusions: The conducted literature review shows that the current COVID-19 pandemic is associated with an increase in the prevalence of symptoms of anxiety disorders in the general population. The multifaceted nature of the issue of anxiety disorders in the COVID-19 pandemic clearly indicates the need to continue research in this area.